Evaluation of Tetrofosmin Cold Kit Fractionation Using Alternative New Method of Quality Control for Testing Radiochemical Purity - Nisha Bhatia; Rakhee Vatsa; Vandana K. Dhingra; Devinder Kumar Dhawan; Vijayta Dani Chadha (World Journal of Nuclear Medicine)
Objective The aim of this study is to establish a method for the fractionation of tetrofosmin cold kit under different storage conditions and to optimize an alternate chromatography method from the reference method to test radiochemical purity (RCP). Materials and Methods Tetrofosmin cold kit vial was fractionated aseptically in six equal fractions and stored in vials and syringes. To test the stability of the reconstituted solution for a longer duration, the mother vials and syringes were stored at two different temperatures, that is, at 4°C and at −20°C till further used. Radiolabeling of fractionated tetrofosmin was performed as per the standard labeling protocol. Radionuclide purity, radioassay, and pH were tested. Radiolabeling efficiency and RCP were determined by paper chromatography. Results Radionuclide purity of eluate was greater than 99.9%. The pH of technetium-99m (Tc-99m) eluate and Tc-99m tetrofosmin was between 4.5–7.5 and 7.5–9.5, respectively. The deviation in the radioactivity during all measurements was less than 1%. The kits fractioned in glass vials resulted in higher radiolabeling yield and RCP as compared with kits fractionated in syringes. The RCP of glass vial versus syringe was observed to be greater than 95 versus 90% and 95 versus 80% at −20°C and 4°C, respectively. Conclusion Tetrofosmin kit can be used in a cost-effective manner by fractionation. One tetrofosmin vial can be used in six fractions for up to 15 days when stored at −20°C and 4°C freezer temperature. The alternative method to check the RCP of Tc-99m tetrofosmin is safer and less time consuming as compared with the reference method.